Tooth development in human evolution and bioarchaeology - Hillson, Simon (Cambridge University Press, 2014)
"Human children grow at a uniquely slow pace by comparison with other mammals. When and where did this schedule evolve? Have technological advances, farming and cities had any effect upon it? Addressing these and other key questions in palaeoanthropology and bioarchaeology, Simon Hillson examines the unique role of teeth in preserving detailed microscopic records of development throughout childhood and into adulthood. The text critically reviews theory, assumptions, methods and literature, providing the dental histology background to anthropological studies of both growth rate and growth disruption. Chapters also examine existing studies of growth rate in the context of human evolution and primate development more generally, together with implications for life history. The final chapters consider how defects in the tooth development sequence shed light on the consequences of biological and social transitions, contributing to our understanding of the evolution of modern human development and cognition"..